Selection of software tools for automation of business planning processes - Abasova, A.; Mamedova, K.; Alekperova, L.; Абасова, А. А.; Мамедова, К. М.; Алекперова, Л. А. (Харківський національний автомобільно-дорожній університет, 2023)
The article discusses the recent significant increase in interest in the practical application of business software (SW). Today, it is clear to everyone that management prospects are in the field of information technology. There are many software products on the market that are used for business software, management, financial and business consulting, enterprise or holding management, project management, business cycle optimization and document cycle automation. The article discusses the selection of software tools for automating business planning processes, as there has been a growing interest in the practical application of business software. Business software can be classified into several categories such as enterprise management systems, accounting software, document management systems, etc. The article emphasizes that the choice of a specific software product is related to its functional features and the environment in which it is used. The article identifies three levels of management, and for each level, different requirements for software are identified. The article divides project management software into two groups, entrylevel programs, and professional systems, and discusses their functionalities and costs. The article concludes that there is an intermediate position for project management software, which integrates features of the first two groups. Furthermore, it is emphasized that domestic developments in project management software are preferred by many users due to their availability and low cost. The article suggests that with project management packages, financial managers can obtain detailed financial plans, financing schemes, and business evaluations for decision making. The article concludes by outlining key factors that must be taken into account when selecting project management software, such as complexity, updating options, scalability, user interface, resources, coding, calculated fields, risk analysis, and task distribution. The article emphasizes the importance of business-planning-analytics packages in helping managers build effective financial models by dynamically simulating time-varying factors.
Вибір програмних засобів для автоматизації процесів бізнес-планування
Keywords: information technologies; management systems; accounting software; document management systems; business consulting; project management; інформаційні технології; системи управління; бухгалтерське програмне забезпечення; системи документообігу; 338.2; 10.30977/ЕТК.2225-2304.2023.41.78